2021
DOI: 10.3390/ma14020309
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Piezoelectric Response in AlN by Yb Addition

Abstract: This study employs first-principles calculations to investigate how introducing Yb into aluminum nitride (AlN) leads to a large enhancement in the material’s piezoelectric response (d33). The maximum d33 is calculated to be over 100 pC/N, which is 20 times higher than that of AlN. One reason for such a significant improvement in d33 is the elastic-softening effect, which is indicated by a decrease in the elastic constant, C33. The strain sensitivity (du/dε) of the internal parameter, u, is also an important fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…In this case, first-principles calculations are considered to be effective for evaluating the physical properties. In previous research, we investigated the piezoelectric characteristics of YbAlN by first-principles calculations, and the calculated results agreed with the experimental results …”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In this case, first-principles calculations are considered to be effective for evaluating the physical properties. In previous research, we investigated the piezoelectric characteristics of YbAlN by first-principles calculations, and the calculated results agreed with the experimental results …”
Section: Introductionsupporting
confidence: 71%
“…The Born effective charges ( Z 33 ) of Al (orange line) and Yb (green line) are plotted against the Yb concentration in Figure b. The average of the Born effective charges of Al and Yb, which was reported in a previous study, is also shown (black line). Although the average value of the Born effective charge increases as the Yb concentration increases, the charge values of Al and Yb also tend to increase.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The latest research report that introduces Yb into aluminum nitride (AlN) leads to a large enhancement in the material's piezoelectric response (d33). The maximum d33 is calculated to be over 100 pC/N, which is 20 times higher than that of AlN (Hirata et al, 2021). However, there are no reports of successful preparation of devices from related materials.…”
Section: Piezoelectric Filmsmentioning
confidence: 89%